Habitat fidelity in hawksbill sea turtles - Andrew S. Maurer; Julia A. Horrocks; Claudio Bellini; Karen L. Eckert; Alexandra L. Fireman; Mariana M. P. B. Fuentes; Barry Krueger; Kathryn E. Levasseur; Maria A. Marcovaldi; Renata M. A. Ramos; Seth P. Stapleton; Hannah B. Vander Zanden; et al. (Ecology, 2025)
Climate change is altering habitat suitability and driving shifts in species distributions. To understand potential responses by mobile animals, it is essential to assess levels of plasticity in habitat use, ranging from transience to long‐term fidelity. Here, we evaluate the fidelity of hawksbill sea turtles ( Eretmochelys imbricata ) to habitats used while foraging (our primary focus), migrating, and nesting. After satellite tracking 17 adult females from three Western Atlantic nesting areas, we then re‐tracked them in a subsequent year. Of 15 turtles with sufficient data to assess interannual foraging area fidelity, 14 returned to the same home range, exhibiting overlap between successive 50% utilization distributions (UDs); the 15th individual shifted

Monitoring the conservation status of sea turtle nesting sites: expert knowledge and quantitative indicators - Paolo Casale; Thomas Arapis; Simona A. Ceriani; Erdal Elginoz; Wayne Fuller; Yakup Kaska; Tonya M. Long; Maria A. Marcovaldi; Dimitris Margaritoulis; Ayşe Oruç; Alexsandro Santos; Doğan Sözbilen; et al. (Journal of Coastal Conservation, 2025)

Tracking green turtle nesting trends at a remote oceanic rookery - Luciana Medeiros; Milani Chaloupka; Alan B. Bolten; Eduardo M. von Muhlen; Alexsandro Santos; Ana C. J. Marcondes; João C. A. Thomé; Maria Ângela Marcovaldi; Karen A. Bjorndal (Marine Biology, 2022)

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Comparison of reproductive output of hybrid sea turtles and parental species - Luciano S. Soares; Alan B. Bolten; Marta L. Wayne; Sibelle T. Vilaça; Fabrício R. Santos; Maria A. G. dei Marcovaldi; Karen A. Bjorndal (Marine Biology, 2017)

Adaptive threat management framework: integrating people and turtles - Valéria R. F. da Silva; Sylvia F. Mitraud; Maria L. C. P. Ferraz; Eduardo H. S. M. Lima; Maria Thereza D. Melo; Armando J. B. Santos; Augusto César C. D. da Silva; Jaqueline C. de Castilhos; Jamyle A. F. Batista; Gustave G. Lopez; Frederico Tognin; João Carlos Thomé; et al. (Environment, Development and Sustainability, 2016)